Rising the Competitiveness of a Cultural Tourist Destination in Banten, Indonesia through Stakeholder Orientation, Strategic Capability, and Shared Value Creation - Titus Indrajaya; FX Setiyo Wibowo; Kadek Wiweka (Budapest International Research and Critics University, 2022)
The objective of this research is to determine the impact of stakeholder orientation, strategic capability, and shared value creation on the competitiveness of cultural tourist destinations. This study was carried out in order to improve the competitiveness of Banten, which has many cultural advantages but has not been fully utilized. This study employs quantitative methods, such as the analysis of structural equation models (SEM), which are supplemented by qualitative data. This research was performed out by distributing electronic questionnaires to 321 respondents from 8 districts and cities, including tourism officials, tour guide associations, tourism pioneer groups, tourism stakeholder’s social media groups, youth groups, and creative entrepreneur’s associations. In addition, focus group discussions with stakeholders were held to balance and strengthen the data collected. According to the results of the concurrent tests, Orientation Stakeholder (OS), Strategic Capabilities (KS), and Shared Value Creation (PNB) all contribute significantly to the competitiveness of cultural tourist destination variables. Remarkably, partial tests revealed that the variety of OS and KS has no effect on the competitiveness variables of cultural tourist destinations (DS). This implies that the indicators of OS, KS, and PNB should be improved in the future, particularly the variable of shared value creation (PNB), which plays an essential role.